IMPROVING THE MECHANISM OF FORMING AND USING EXTRA-BUDGETARY FUNDS IN BUDGETARY ORGANIZATIONS - Boymirzayev Kobiljon Yokubjon ugli (Modern American Journals, 2025)
This article analyzes the theoretical, legal, and practical foundations of forming and using extra-budgetary funds in budgetary organizations. It examines the main sources, mechanisms, and principles for effective fund utilization. The study highlights the importance of improving financial autonomy, transparency, and accountability through digitalization and performance-based management. The research results can be used to enhance the efficiency of public institutions and improve the financial sustainability of the public sector.
Keywords: Budgetary organization, extra-budgetary funds, financial mechanism, public finance, digitalization, efficiency, transparency.